2020
DOI: 10.1101/2020.07.01.181735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The structure of enteric human adenovirus 41 - a leading cause of diarrhea in children

Abstract: AbstractHuman adenovirus (HAdV) types F40 and F41 are a leading cause of diarrhoea in children, a prominent cause of childhood mortality worldwide. Here we present the first structure of an enteric HAdV – HAdV-F41 – determined by cryo-EM to a resolution of 3.8Å. The structure reveals extensive alterations to the virion exterior as compared to respiratory and ocular HAdVs, including a unique arrangement of capsid protein IX. In other HAdVs, this protein forms a rigid, virion-cov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 67 publications
(89 reference statements)
0
18
0
1
Order By: Relevance
“…Particles were manually picked and subjected to reference-free 2D classification and well-resolved classes were combined and subjected to mask-less three-dimensional (3D) classification, applying icosahedral symmetry [I3 according to Crowther ( 68 )]. A low-pass–filtered (30 Å) volume of HAdV-F41 ( 69 ) was used as a reference volume. Particles were classified into two classes, resulting in 93% of particles allocated to one well-resolved class which was used for downstream processing.…”
Section: Methodsmentioning
confidence: 99%
“…Particles were manually picked and subjected to reference-free 2D classification and well-resolved classes were combined and subjected to mask-less three-dimensional (3D) classification, applying icosahedral symmetry [I3 according to Crowther ( 68 )]. A low-pass–filtered (30 Å) volume of HAdV-F41 ( 69 ) was used as a reference volume. Particles were classified into two classes, resulting in 93% of particles allocated to one well-resolved class which was used for downstream processing.…”
Section: Methodsmentioning
confidence: 99%
“…These observations indicate that the triskelion motif is critical for capsid binding, while the triskelion-carrying proteins are hotspots for AdV evolution, linked to capsid stabilization, interaction with host factors (because of their accessible location on the capsid surface) and consequently, tropism. Indeed, even within HAdVs, protein IX variations may be related to tropism determination, as recently shown by the structure of the enteric HAdV-F41 (Pérez-Illana et al, 2020;Rafie et al, 2020).…”
Section: Discussionmentioning
confidence: 81%
“…Alternatively, U1 and U2 may correspond to the genus specific proteins LH2 and p32k. We favour this last possibility, since the other candidates are also present in mastadenoviruses, but no equivalent densities have been detected in the structures solved so far (Dai et al, 2017;Liu et al, 2010;Pérez-Illana et al, 2020;Rafie et al, 2020;Yu et al, 2017). Both LH2 and p32k have positive charge (isoelectric point 11.02 for p32k, 8.59 for LH2) suggesting they interact with the genome, and are predicted to be predominantly α-helical.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, structural studies of the enteric adenovirus Ad-F41 short fiber head revealed a loop in the fiber head that was disordered at neutral pH and ordered at pH 5 (51, 52). Moreover, comparison of the Ad-F41 capsid to that of non-enteric adenoviruses highlighted a surface with relatively few charged residues and an almost unaltered structure at pH 4 (53)…”
Section: Discussionmentioning
confidence: 99%